Stabilizing the electroluminescence of halide perovskites with potassium passivation - Kanwat, Anil (2020)
Halide perovskites are of great interest for light-emitting diodes (PeLEDs) in recent years due to their excellent photo- and electroluminescence properties. However, trap/defects and ion migration of devices under high external driving voltage/current are yet overcome. In this work, it is found that upon potassium (K) addition to a CsPbBr3/Cs4PbBr6 (3D:0D = 0.85:0.15) perovskite, a locally-disordered 0D Cs4-xKxPbBr6 phase is formed with nearly 0.35:0.65 admixture of 0D:3D, along with an unreacted KBr phase potentially passivating the surface and grain boundaries. The formation of CsPbBr3 nanocrystals (~10nm) confined within the Cs4-xKxPbBr6 matrix accompanied by larger CsPbBr3 grains (~50nm) is further confirmed by high-resolution transmission electron microscopy. In addition, the kinetics of ion migration were characterized with Auger electron spectroscopy and double-layer polarization using capacitive-frequency measurements, revealing significantly lower hysteresis, halide ion migration and accumulation for the K-incorporated samples during device operation, resulting in substantial improvements in LED performances and stability.